"Textile Progress 2005, Vol.37 No 1/2: Critical Solutions in the Dyeing of Cotton Textile Materials" - Shamey (R); Hussein (T) (2005)
Textile Progress 2005 ; Dyeing ; Cotton Textile Materials
8.5
Keywords: Textile Progress 2005 ; Dyeing ; Cotton Textile Materials